Twitter sentiment analysis about economic recession in indonesia - Eka Putra, Fauzan Prasetyo; Maulana, Fairuz Iqbal; Akbar , Nawawi Muhammad; Febriantoro, Wicaksono (Bulletin of Social Informatics Theory and Application, 2023)
As one of the most popular social media platforms, Twitter enables users to express their opinions on diverse concepts, products, and services. Large quantities of data shared as tweets can be mined for user feedback and used to improve the quality of products and services. Using Twitter data and social media sentiment analysis, tracking how people feel about the recession in real time is possible. As a consequence, relevant organizations or governments can take preventative measures against the disinformation and unlawful conduct caused by the effects of the recession. This study aims to determine if there is a correlation between how people on Twitter feel about the recession. This study's data acquisition utilized "Recession"-tagged Twitter remarks from 2023. This study analyses filtered tweets for sentiment, emotion, word usage, and trends. According to the findings, 94% of tweets had benign sentiments, 4% had positive sentiments, and 2% had negative sentiments. Tweets with moderate subjective valence cluster in the middle of the polarity scale (between 1 and +1), while tweets with strong subjective valence are dispersed throughout the scale